Glioblastoma multiforme of the conus medullaris with leptomeningeal dissemination that presented as intracranial hypertension: A case report and literature review - Yu Hu (Wolters Kluwer Medknow Publications, 2021)
Spinal glioblastoma multiforme (GBM) that originates from the conus medullaris is rare as only 28 cases have been reported. It is highly aggressive and usually initially presents with low back pain, sensory and motor impairment of the lower extremities, and bladder dysfunction. We herein report a unique case of GBM in the conus medullaris with leptomeningeal dissemination that initially presented with increased intracranial pressure without hydrocephalus. The patient was first diagnosed with tuberculous meningitis and received antituberculosis therapy, but the symptoms did not resolve and even worsened. Subsequent radiological imaging clearly disclosed an intramedullary lesion at the T12 level with the progression of leptomeningeal enhancement. Subtotal resection of the intramedullary lesion was performed, and pathological examination revealed the presence of GBM. To our knowledge, our case was the first with holocordal and intracranial leptomeningeal dissemination that initially presented with intracranial hypertension in the absence of hydrocephalus. Awareness of this unusually lethal condition is significant for proper diagnosis, timely treatment, and consideration of clinical prognosis.